Citric acid, chitosan and oregano essential oil impact on physical and antimicrobial properties of cassava starch films - Hernandez Nuñez, Maury Sabrina (2023)
The research deals with the development of antimicrobial edible films based on cassava starch/glycerol, added with oregano essential oil and prepared by casting. The effect of citric acid and chitosan content on the film´s physical properties was studied using a response surface methodology. It was generally found that citric acid acted as a plasticizer while chitosan reinforced the film matrix, depending on the amount involved. One film formulation was selected for its high stress at break (σb, 15±1 MPa) and low solubility in water (SW, 12.8±0.3 %). In the second step, the influence of citric acid or oregano oil presence on the properties of the biopolymer matrix was investigated. The thermal stability, chemical interactions, water vapor permeability (WVP), microstructure and antimicrobial activity of the optimized film were compared with control systems formulated with starch/glycerol/chitosan, starch/glycerol/chitosan/citric acid or starch/glycerol/chitosan/oregano oil. The citric acid addition increased σb, WVP and thermal resistance while oregano oil improved the WVP but produced irregularities in the microstructure of the starch/glycerol/chitosan matrix. Moreover, the presence of oregano oil generated a very efficient antimicrobial film against external contamination by Zygosaccharomyces bailii. This research confirms that developed films are a relevant alternative for the production of biodegradable active packaging.